2011
DOI: 10.1039/c1sm06430d
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of nanofibres with parallel line surface texture for improvement of nerve cell growth

Abstract: † Electronic supplementary information (ESI) available: Experimental details, SEM images, polarized FTIR spectra, WAXs patterns and calculation of the surface area. See

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
0
57
0
Order By: Relevance
“…32 In this study, we develop a novel technique to directly electrospin nanofibers into a fibrous NGC and control the nanofibers to align along the longitudinal direction. By using cellulose acetate butyrate (CAB) as model polymer, the nanofibers in the NGCs can have either a smooth surface or nano-sized longitudinal grooves on the surface, depending on the molecular weight of the polymer used for electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…32 In this study, we develop a novel technique to directly electrospin nanofibers into a fibrous NGC and control the nanofibers to align along the longitudinal direction. By using cellulose acetate butyrate (CAB) as model polymer, the nanofibers in the NGCs can have either a smooth surface or nano-sized longitudinal grooves on the surface, depending on the molecular weight of the polymer used for electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…The disc‐electrospun nanofibers looked uniform in fiber morphology and contained no beads, which were similar to those electrospun from the needle electrospinning. At the concentration of 12%, CAB was electrospun into smooth fibers without a parallel‐grooved surface feature 26. The needle‐electrospun nanofibers had an average diameter of 367 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts were selected as they can be easily regulated by the contact guidance from culture substrates 27. Our previous study has found that Schwann cells exhibiting prompt proliferation on electrospun CAB nanofibers and the growth behavior could be readily regulated though the control of fiber orientation 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the spinneret structure, collecting mode and operating parameters, they can have aligned fibrous structures [6], bicomponent cross-sectional configurations [7,8], ribbon shapes [9] or porous surfaces [10]. In our previous study, we have found that nanofibers with a parallel line surface texture can be electrospun from a polymer solution when a mixed solvent system consisting of a highly volatile solvent (e.g., acetone) and a high boiling point organic solvent are employed [11]. The highly-ordered surface texture on the fibers was found to be beneficial to the growth of nerve cells regardless of the fiber orientation.…”
Section: Introductionmentioning
confidence: 99%